Stabilization and Event-Triggered Control of Stochastic Delay Systems With Markovian Jump Parameters - Chunjie Xiao (IEEE Access, 2020)
This article is concerned with the problem of delay-dependent stabilization for a class of stochastic Markov systems with event-triggered feedback control. An event-triggered mechanism (ETM) is proposed with the purpose of effectively reducing the transmissions of redundant massages, in which the generation of sensor sampling and control actuation is not periodic but only when some event-driven conditions are satisfied. In the meanwhile, a novel Lyapunov-Krasovskii functional (LKF) is applied to the closed-loop systems to establish the criterion of practically exponential mean-square stability. And a positive lower bound on the inter-execution times is guaranteed, that is, the Zeno behavior will not happen under this ETM. Furthermore, the event-triggered feedback controller can be constructed by solving the relevant linear matrix inequalities (LMIs). In the end, a numerical example displays the feasibility of our results.